Agility and supply chain management: issues and challenges - Abdul Aziz, Ahmad Kamil; Abd Rahman, Azmawani; Kamarulzaman, Nitty Hirawaty; Sambasivan, Murali (2014)
In the global supply chain, the potential of agility for growth is very promising. Despite of the remarkable expansion of the industry, especially in the Asia Pacific region; there has been very little published research in the area of agility and supply chain resulting in very limited dissemination of information for the purpose of advancement, learning and integration. The purpose of this paper is to examine the issues and challenges faced by the practitioners as well as the relevant parties involved in the industry. By reviewing the agility and supply chain management literature, this study found three key issues and problems, namely the procurement/sourcing agility, manufacturing agility and logistics/distribution agility. These issues have been the hindrance to agility effectiveness. This paper attempts to open up various issues surrounding this complex and fragmented industry. It thus, provided a base for future researchers to examine any aspects of agility and supply chain management.